Konsep Asnaf Penerima Zakat Menurut Pemikiran Yusuf Al-Qardawi dan Wahbah Al-Zuhayli: Sebuah Analisis Komparasi - Intan Sherly Monica; Atik Abidah (Jurnal Antologi Hukum, 2021)
Abstract: This article discusses the Asnaf zakat according to contemporary scholars, namely Yusuf Al-Qardawi and Wahbah Al-Zuhayli. This work aims to explain the similarities and differences in the thoughts of the two figures regarding asnaf zakat. The method used is library research by examining the books of the two figures, namely Fiqhuz Zakat and Islamic Fiqh wa Adilatuhu. It can be concluded that the thoughts of Yusuf Al-Qardawi and Wahbah Al Zuhayli on the eight groups of zakat recipients are not much different. It's just that there is a slight difference that is most significant in the fi sabilillah group where Yusuf Al Qardawi argues that this group is extended to the meaning of fighting in the way of Allah such as charity for the public interest, this is in accordance with the opinion of some scholars who expand the meaning of fi sabilillah. Meanwhile, according to Wahbah Al-Zuhayli the meaning of fi sabilillah is soldiers who fight but are not paid by the state, this is in accordance with Q.S ash-Shaff: 4. And from their opinion, Yu>suf Al Qard{awi's thoughts are the most relevant to the condition of the Indonesian state. The istinbath method used by the two figures is dominant in ijma'. And what influenced his thinking the most was the role of the teacher and the social conditions of the two figures.